Phenylketonuria: A new look at an old topic, advances in laboratory diagnosis, and therapeutic strategies - Sumaily, Khalid M.; Mujamammi, Ahmed H. (International Journal of Health Sciences, 2017)
Disorders of protein metabolism are the most common diseases among discovered inherited metabolic disorders. Phenylketonuria (PKU), a relatively common disorder that is responsive to treatment, is an inherited autosomal recessive disorder caused by a deficiency in phenylalanine hydroxylase (PAH) or one of several enzymes mediating biosynthesis or regeneration of the PAH cofactor tetrahydrobiopterin. The objective of this review is to discuss therapeutic strategies that have recently emerged for curing patients with PKU, which have demonstrated promising improvements in managing these patients. Data sourcing included a systematic literature review of PubMed with a focus on emerging knowledge pertaining to this well-studied disease. Recent advances in laboratory diagnosis and therapeutic strategies were described. Collectively, promising and rapid enhancements in neonatal diagnostic technologies and recently emerged therapeutic strategies are paving the way for early diagnosis and treating many inborn errors of metabolism, such as PKU.